Literature Study of Communication Problem Intervention in Autistic Students - Al'azmi, Nilna Uffi; Hidayat, Erfin Chandra Dwi; Nursalim, Mochamad (Jurnal ORTOPEDAGOGIA, 2025)
Communication problems are a major challenge faced by students with autism spectrum disorders (ASD). This literature study aims to explore various intervention approaches that have been used to address communication problems in autistic students. The research method used is a systematic literature review of various scientific journals published between 2013 and 2023. The results of the study indicate that approaches such as Applied Behavior Analysis (ABA), Picture Exchange Communication System (PECS), speech therapy, social stories, and video modeling have proven effective in improving the communication skills of autistic students. These findings are expected to be a reference for educational practitioners and therapists in choosing appropriate intervention strategies.